PERANCANGAN SISTEM INSENTIF DOKTER SPESIALIS BERBASIS KINERJA PELAYANAN BPJS KESEHATAN DI RUMAH SAKIT CAHYA KAWALUYAN - Goey, Hendra William; Talim, Margaretha Banowati; Sukoco, Lisda (Business Administration Department - Universitas Katolik Parahyangan, 2024)
Hospitals in the National Health Insurance (JKN) era face challenges due to the shift in payment methods from retrospective (Fee for Services) to prospective (case-based payment). This change drives efficiency improvements without compromising service quality.This study formulates a performance-based incentive system for specialist doctors to enhance the efficiency and quality of BPJS Kesehatan patient services at RS Cahya Kawaluyan. Using a case study approach and both quantitative and qualitative analysis methods, the incentive system is designed with the Ongoing Professional Practice Evaluation (OPPE) as a performance measurement tool.The study results propose an incentive system based on individual performance, measurable indicator-based evaluations, periodic payments, and collaboration between the Medical Committee and the Human Resources Department. Doctors' performance is assessed using nine key indicators, with patient satisfaction and regulatory compliance being the most crucial indicators.To enhance the effectiveness of the incentive system, regular patient satisfaction surveys, regulatory compliance monitoring, and improved time management for doctors are recommended. System optimization can be achieved through integration with the hospital information system, strengthening interdepartmental collaboration, and conducting socialization and training programs. System implementation is expected to drive efficiency, motivation, and improved service quality among specialist doctors at RS Cahya Kawaluyan